FAKTOR PENENTU KESADARAN KONSUMEN DALAM PEMBELIAN PRODUK KERTAS BERTANDA ECO-LABEL - Naniek Utami Handayani; Hery Suliantoro; Satria Dani Ansari (Universitas Mercu Buana, 2018)
Environmental issues developed rapidly driven by the high impact on environmental damage due to the production process that is not environmentally friendly. The increase of goods and services consumption that are quite high throughout the world has resulted in a reduction in natural resources that have an impact on the environment. Efforts to reduce this impact are the existence of a green consumption policy. In 2006, Indonesia introduced eco-label markers on products that have been produced environmentally friendly. This policy needs to be supported by increasing consumer awareness to buy eco-labeled products. This study purposes to identify factors that influence consumer awareness in purchase eco-labeled paper products. This study uses the Structural Equation Modeling, while data processing uses AMOS software. The results showed that the higher the consumer's concern about the state of the environment would be to increase a proper assessment for the environment (environmental attitude), and ultimately the consumer would consciously consume products that have a minimal impact on the environment (environmentally conscious purchasing behavior). Recommendations that can be given to increase consumer awareness in purchasing eco-labeled products, including the use of mass media; environmental education; always socializing to the public regarding environmental issues; provide training to producers